Rabbit's gift : a fable from China - Shannon, George; Dronzek, Laura (Orlando, Fla. : Harcourt, 2007)
Woodland animals, each thinking of his neighbor, share a turnip left on their doorstep.
2.5
K-3
Keywords: Fables; Folklore -- China; Fables; Folklore; Fables; Folklore